Influence of Temperature and Stirring Duration on the Solubility Kinetics of Palm Sugar (Arenga Pinnata) in Water: Implications for Food Processing Efficiency - Rafidah Almira Samosir; Alfira Julian Pratiwi; Ekin Dwi Arif Kurniawan; Mutia Ardila; Trimutia Wulandari; Flia Arnesta Sipayung; Dira Rahma Cahya; Nove Briani Minar Sihombing; Einstenia Sirait; Moondra Zubir; Abd Hakim S (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Palm sugar (Arenga pinnata) is widely used in traditional and industrial food processing, where its solubility plays a crucial role in determining product consistency and efficiency. However, most previous studies have focused on the solubility of refined cane sugar, leaving limited understanding of how temperature and stirring conditions affect the dissolution behavior of palm sugar, which has a more complex composition. This study aims to examine the effect of temperature, solute mass, and stirring duration on the solubility of palm sugar in water. A laboratory-based experimental method was employed, varying temperature (50°C, 75°C, 100°C), sugar mass (20 g and 40 g), and stirring duration (1 and 2 minutes). In general, the findings indicate that higher temperature accelerates the dissolution rate, while greater solute mass extends dissolution time. These results confirm temperature as the dominant factor influencing dissolution kinetics. The implications of this study include improving household practices for faster sugar preparation, optimizing processing efficiency in small-scale food industries, and contributing to food science education by providing an applied example of solubility principles.